REVITALIZATION OF RESEARCH AND DEVELOPMENT SERVICES BASED ON INFORMATION TECHNOLOGY IN CENTRE FOR CLIMATE CHANGE AND POLICY RESEARCH AND DEVELOPMENT - Kirsfianti Linda Ginoga (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Government Regulation No. 12/2014 and Ministry of Forestry Regulation No. 92/Menhut-II/2014 about the types and rates of non-tax tariff from Ministry of Forestry are the underlying motivations to revitalize services in research and development through information technology (IT). Revitalization policy is expected to increase effectiveness, efficiency, value added, professionalism, governance, as well as avoid overlapping research on climate changes in forestry. Using gap and stakeholder analysis, it reveals that a set of technical and administrative tools such as an improved web design and various of SOPs for monitoring and evaluation of services are still needed. Stakeholder analysis through several focus group discussions also shows that there are many stakeholders who are promoters of revitalization that require intensive cooperation, followed by defenders who require periodical information. Stakeholder latent in this program is relatively very minimal. Observation in Centre for Climate Change and Policy Research and Development reveals that in the short term the number of users of services and activities of research and development after revitalization policy in September 2014 increased 143 and 400 percent compared to the same month in 2013, while in October 2013 increased by 300 and 500 percent, respectively compared to October 2014.